2011
DOI: 10.1074/jbc.m110.139139
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Deficiency Attenuates Adipose Tissue Differentiation and Inflammation in Mice

Abstract: Obesity is associated with a variety of disorders and is a significant health problem in developed countries. One factor controlling the level of adiposity is the differentiation of cells into adipocytes. Adipocyte differentiation requires expression of peroxisome proliferator-activated receptor ␥ (PPAR␥), which is activated by ligands to regulate expression of genes involved in adipocyte differentiation. Although 15-deoxy-⌬(12,14)-prostaglandin (PG) J 2 (15d-PGJ(2)) has long been known to be a potent activato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
76
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 53 publications
3
76
3
Order By: Relevance
“…Although prior studies have demonstrated that experimental induction of obesity reduces EETs in liver, kidney, and mesenteric arteries ( 21,31 ), as well as alters cyclooxygenase-mediated prostaglandin biosynthesis and lipoxygenase-mediated leukotriene biosynthesis in adipose tissue ( 32,33 ), the impact of obesity on EET bioavailability in adipose tissue has not been rigorously investigated . Consequently, we employed a metabolomic approach to characterize the global eicosanoid profi le during adipocyte differentiation in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior studies have demonstrated that experimental induction of obesity reduces EETs in liver, kidney, and mesenteric arteries ( 21,31 ), as well as alters cyclooxygenase-mediated prostaglandin biosynthesis and lipoxygenase-mediated leukotriene biosynthesis in adipose tissue ( 32,33 ), the impact of obesity on EET bioavailability in adipose tissue has not been rigorously investigated . Consequently, we employed a metabolomic approach to characterize the global eicosanoid profi le during adipocyte differentiation in 3T3-L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this view, mice genetically deficient for mPGES-1 show basal elevations in PPAR␥ expression and transcriptional activity (17). However, more recent studies have shown that transgenic mice overexpressing COX-2 do not exhibit changes in PPAR␥ expression in adipose tissues (18), although PPAR␥ expression has been shown to be significantly reduced in adipose tissue from COX-2-deficient mice (19). The existence of this undefined role of the COX-2/mPGES-1/PGE 2 pathway in WAT physiology led us to investigate the functional interaction between PPAR␥ and mPGES-1 in the process of adipogenesis.…”
mentioning
confidence: 89%
“…Studies conducted on 3T3-L1 cell lines showed that different adipocyte specific markers which includedPPARγ andadiponectinwere found to be decreased after the use of COX inhibitors (Mazid et al, 2006). COX-2 deficient murine models which were supplied with a high fat dietshowed lower body mass than their wild type counterparts were also found to have higher metabolic activity, lower PPARγ, lower inflammatory markers and significantly higher levels of adiponectin (Ghoshal et al, 2011).These variables coincide with other findings linking them to increased lipolysis and lower body fat and BMIthus suggesting that the use of a COX-2 inhibitor (such as paracetamol) can possibly provide a protective treatment opportunity against obesity and can be employed for future anti-obesity medication. However a minor percentage of opposing research showed an activation of PPARγ in adipocyte cell lines when treated with non-steroidal antiinflammatory (NSAID) drugs such as Indomethacin (Lehmann et al, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Archadionic acid is first released by phospholipases (PLA 2 s) and undergoes conversion to PGH 2 by one of the two COX isozymes (COX-1 or COX-2). The PGH 2 that is produced is metabolized into different PG's that are involved in adipocyte differentiation which causes the activation of PPARγ (Ueno et al, 2011;Ghoshal et al, 2011). Therefore, bearing this expression mechanism in mind-the inhibition of COX-2 would prevent or decrease the conversion of archadionic acid to PGH 2 which will have the ultimate effect of reducing and/or inhibiting adipocyte differentiation.COX-2 activation has also been found to be significantly involved in development of an inflammatory response in adipose tissue (Hsieh et al, 2010) and has been linked to contributing in brown adipocyte differentiation in mice (Ghoshal et al, 2011).…”
Section: Introductionmentioning
confidence: 99%